Immobilization of Trifluoromethyl-Substituted Pyridine-Oxazoline Ligand and Its Application in Asymmetric Continuous Flow Synthesis of Benzosultams - Kocúrik, Martin; Bartáček, Jan; Drabina, Pavel; Váňa, Jiří; Svoboda, Jan; Husáková, Lenka; Finger, Vladimír; Hympánová, Michaela; Sedlák, Miloš (American Chemical Society, 2023)
This study presents an improved synthetic route to ligand (S)-4-(tert-butyl)-2-(5-(trifluoromethyl)pyridin-2-yl)-4,5-dihydrooxazole and its application as a highly active and enantioselective catalyst in the addition of arylboronic acids to cyclic N-sulfonylketimines. Immobilization of such a ligand was achieved using a commercially available starting material and a PS-PEG TentaGel S NH2 support, resulting in a stable heterogeneous catalyst. Although the anchored catalyst exhibited a slight reduction in enantioselectivity and a 4-fold decrease in reaction rate, it displayed remarkable stability, enabling 10 consecutive reaction cycles. Furthermore, the successful transition to a continuous flow system demonstrated even higher turnover numbers compared to batch arrangements. These findings provide valuable insights into the development of efficient flow reactors for continuous synthesis of benzosultams, further advancing the field of asymmetric catalysis.
Imobilizace trifluormethyl-substituovaného pyridin-oxazolinového ligandu a jeho aplikace v asymetrické kontinuální syntéze benzosultamů
Keywords: catalyzed enantioselective addition; arylboronic acids; arylation; ketimines; benzosultams; continuous flow synthesis; katalyzované enantioselektivní adice; arylboronové kyseliny; arylace; ketiminy; benzosultamy; kontinuální průtoková syntéza